Job Crafting, Performance, and the Mediating Role of Gratitude: A Study Among the Sales Service Personnel of Tourist industry, India - Bala Subramanian R; Subhajit Bhattacharya; Munsih Thakur (Centre For Tourism Planning and Development, 2022)
Job crafting plays a key role in many aspects of the job. Providing support and autonomy to craft the job, makes the employees grateful and influences job related outcomes. We intended to examine the mediating role of gratitude on the relationship between job crafting and job performance. We surveyed the salesperson of tourism and hospitality organizations in India. Results showed that job crafting positively influences job performance mediated by the emotion of gratitude. Key theoretical and practical implications of our study are discussed followed by direction for future research.